2021
DOI: 10.3390/ijerph19010259
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide Research on Environmental and Human Exposure and Risks in Sub-Saharan Africa: A Systematic Literature Review

Abstract: On the African continent, ongoing agriculture intensification is accompanied by the increasing use of pesticides, associated with environmental and public health concerns. Using a systematic literature review, we aimed to map current geographical research hotspots and gaps around environmental and public health risks research of agriculture pesticides in Sub-Saharan Africa (SSA). Studies were included that collected primary data on past and current-used agricultural pesticides and assessed their environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 106 publications
0
20
0
Order By: Relevance
“…This may suggest that the isomers of HCH which were detected in this study were recently applied. The use may be put into malaria control, agricultural, or industrial [ 3 ]. Generally, if the ratio of δ -HCH to γ -HCH concentrations in sediment is below 3, it suggests that the source of HCH to the aquatic ecosystem is a new input [ 29 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This may suggest that the isomers of HCH which were detected in this study were recently applied. The use may be put into malaria control, agricultural, or industrial [ 3 ]. Generally, if the ratio of δ -HCH to γ -HCH concentrations in sediment is below 3, it suggests that the source of HCH to the aquatic ecosystem is a new input [ 29 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Increasing pesticide use and misapplications of pesticides along river basins pose serious threats to aquatic ecosystems [ 1 , 2 ]. Increasing incidence of vector diseases is contributing to increasing use of pesticides [ 3 5 ]. Pesticides are mostly used by farmers in the rainy season to control pests [ 6 – 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To prepare for the workshop, two main activities were conducted. First, a systematic literature review was conducted to map current geographical research hot spots and identify gaps around environmental and public health risks associated with agriculture pesticide use in the Africa Region [ 26 ]. In this review, 391 articles published between 2006 and 2021 were identified that covered 469 study sites with five geographical research hot spots (two in South Africa, two in East Africa, and one in West Africa).…”
Section: Methodsmentioning
confidence: 99%